MODELLING DISTRIBUTION AND TRANSPORT PROCESSES OF RED ANCHOVY FISH EGGS AND LARVAE (Encrasicholina punctifer) IN THE UPWELLING WATERS OF SOUTH CENTRAL VIET NAM - Quang, Vo Van; Chung, Tran Van (Vietnam Journal of Marine Science and Technology, 2012)
Distribution of fish eggs and larvae of red anchovy is variable in July 2003, April 2004, July 2004 and March 2005 in the upwelling waters of Vietnam. The upwelling process marked to the responses of adult who released the eggs in the strong upwelling period (June - August). The density of fish eggs of red anchovy are most abundant in the southwestern monsoon (July 2003 & 2004). Although the difference between the climatic means during all seasons, a clear tendency exists with high density of fish eggs in spawning ground of inshore waters (stations: 41, 42, 51, 52, 62, and 63). The distribution of larvae is different in comparison with eggs that demonstrate the influence of circulation of the mass waters through diffusion, transport and retention of larvae into the coastal zone such as bays and islands where are successfully for recruitment process of red anchovy population.